2003
DOI: 10.1002/jcla.10075
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐6‐phosphate dehydrogenase deficiency does not result from mutations in the promoter region of the G6PD gene

Abstract: In this study, we investigated whether glucose-6-phosphate dehydrogenase (G6PD) promoter mutations are responsible for G6PD deficiency. We analysed the G6PD proximal promoter and the 5' untranslated region (UTR) in 65 G6PD-deficient individuals, in which no mutations have been found in the G6PD gene coding sequences, using a nonradioactive polymerase chain reaction/single-strand conformation polymorphism (PCR/SSCP) analysis. We identified no sequence variations in the G6PD core promoter or in the 5' UTR of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although Menousos et al . [ 71 ] tried to associate promoter G6PD mutations with deficient cases, no correlation was found.…”
Section: Focusing On Molecular Levelmentioning
confidence: 99%
“…Although Menousos et al . [ 71 ] tried to associate promoter G6PD mutations with deficient cases, no correlation was found.…”
Section: Focusing On Molecular Levelmentioning
confidence: 99%
“…Correct promoter functioning is needed for the proper expression of G6PD that is under the control of some unidentified specific factors and elements [31] . However, no sequence variations were identified in previous studies [32] in the G6PD core promoter or in the 5′UTR of G6PD deficient individuals who had no mutations in their exons 2-13. Human G6PD gene, as a housekeeping gene, has at least 9 GC boxes in its regulatory 5′-flanking sequence and its promoter function depends on 2 GC boxes that are cell specifically controlled [33] .…”
Section: Discussionmentioning
confidence: 59%
“…This may be due to mutations that occur in other regions of the gene that were not investigated in this study, such as mutation in the intronic flanking regions, or cryptic mutations in the promoter region [ 20 , 24 ]. Another possible explanation is epigenetic mechanisms that influence gene transcription [ 25 ]. Toniolo et al [ 26 ] reported G6PD expression to be associated with the methylation status of the promoter CpG island.…”
Section: Discussionmentioning
confidence: 99%